2009
DOI: 10.1378/chest.09-0597
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Treatment of Obstructive Sleep Apnea During Decompensation of Heart Failure

Abstract: Background: Treatment of obstructive sleep apnea (OSA) in outpatients with systolic heart failure improves cardiac function. We evaluated the impact of immediate inpatient diagnosis and treatment of OSA in hospitalized patients with acutely decompensated heart failure (ADHF) on in-hospital cardiac outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 39 publications
0
33
0
2
Order By: Relevance
“…Moreover, studies using auto-CPAP have shown that it improves left ventricular ejection fraction in patients with heart failure. 24 In addition, most of the subjects in this study had obstructive sleep apnea, and auto-CPAP is indicated in those patients.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, studies using auto-CPAP have shown that it improves left ventricular ejection fraction in patients with heart failure. 24 In addition, most of the subjects in this study had obstructive sleep apnea, and auto-CPAP is indicated in those patients.…”
Section: Discussionmentioning
confidence: 86%
“…22 Moreover in heart failure patients, treating SDB with CPAP increases left ventricular ejection fraction by 2% to 8%. [23][24][25] The 2013 report from the American College of Cardiac Foundation/American Heart Association Task Force on practice guidelines for the management of heart failure supports the use of PAP in patients with heart failure. 26 This report indicated that PAP has been shown to increase ejection fraction and improve functional status in patients with heart failure and sleep apnea.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…A previous study has noted the value of PM in hospitalized patients. 19 However, PM can be expensive due to logistic and technical support requirements. Many smaller facilities in the community may not have these resources.…”
Section: 14mentioning
confidence: 99%
“…In HF patients following recovery from acute decompensation, the presence or absence of SDB may play key roles in determining whether PAP therapy should be considered. Although most previous data regarding SDB in HF and its treatment with PAP mentioned earlier involve HF patients in the chronic phase, it was recently reported that hospitalized HF patients following ADHF frequently develop SDB and that the presence of SDB during hospitalization following ADHF is a predictor of readmission and mortality [116][117][118] . Thus, PAP therapy should be considered even for hospitalized HF patients, especially in the setting of symptomatic SDB.…”
Section: Hf Patients Following Acute Decompensationmentioning
confidence: 99%
“…Thus, PAP therapy should be considered even for hospitalized HF patients, especially in the setting of symptomatic SDB. One study suggests a beneficial effect of in-hospital bi-level PAP (with S-mode) therapy for OSA on improvement of cardiac function following ADHF [117] . An ongoing study may elucidate whether PAP therapy improve outcomes in these patients [119] .…”
Section: Hf Patients Following Acute Decompensationmentioning
confidence: 99%